Is Age ≥ 55 years an optimal cutoff point among patients with differentiated thyroid Microcarcinoma? a preliminary study. (July 2022) - Min, Yu; Feng, Yang; He, Danshuang; Zeng, Xuan; Fan, Shenghao; Luo, Haojun; Yin, Guobing; Hu, Daixing
Highlights: This is large population-based study on 25, 086 DTMC patients. 55 years might not be the best cutoff point for DTMC patients. 65 years could be more suitable for the risk stratification in DTMC patients. patients with age > 65 years, ETE, N1b, and M1 status had worse prognosis. Abstract: Purpose: Age ≥ 55 years is regarded as a pivotal component of TNM stage classification in differentiated thyroid carcinoma (DTC). However, whether this cutoff point is still adaptable for differentiated thyroid microcarcinoma (DTMC) is rarely investigated. Methods: We reviewed and analyzed the data of DTC patients aged ≥ 55 years from the Surveillance, Epidemiology, and End Results (SEER) database. Univariate and multivariate Cox regression analyses were used to determine the potential risk factors of cancer-specific survival (CSS) in DTMC patients aged ≥ 55 years. The Kaplan-Meier survival curves were used to estimate CSS probability. Receiver operating characteristic (ROC) curves were used to analyze the best age cutoff point for DTMC. Results: Among the DTMC patients, there was no significant difference in the 1-, 3-, 5-, and 7-year CSS probability between the 55–59 years and 60–64-years subgroup (p = 0.72). The ROC curves indicated that 65 years, 65 years, and 64 years were the cutoff age point of 3-, 5-, and 7-year CSS probability in DTMC patients, respectively. Besides, N1b (Hazard ratio (HR) = 3.90, 95% Confidence interval (CI): 2.01–7.57; p < 0.001), extrathyroidal extension (HR = 2.53, 95 %CI: 1.39–4.62; p = 0.002), and M1 (HR = 11.42, 95 %CI: 5.04–25.90; p < 0.001) were the independent risk factors in CSS of DTMC patients. Conclusions: Our results suggested age at diagnosis ≥ 55 years is not the best cutoff point in stratifying the stage of the DTMC patients. On the contrary, those patients aged above 65 years have a significantly lower probability of CSS, which perhaps should be taken into consideration for treatment decision-making.